Analysis of Teacher Creativity Enhancement: The Role of Teacher Involvement in the Creative Process - Haumahu, Cynthia Petra; Korlefura, Criezta; Tupamahu, Kevin Hermanto (International Journal of Education, Information Technology, and Others, 2023)
Teacher creativity has become an indispensable requirement for survival and competitiveness in today's education world. Responding to this emergency situation, current research is focused on investigating the effect of teachers' involvement in the creative process on their creativity. The target population of this research is teachers in Ambon City, and structural equation modeling is used to test the theoretical model and the proposed hypotheses. The results of the study show that involvement in the creative process which consists of identifying problems, seeking information and generating ideas has a positive and significant effect on increasing teacher creativity. These findings suggest that creativity can be enhanced if a teacher is willing to spend the necessary time and effort to thoroughly identify an issue, seek extensive information, and generate many ideas from different perspectives i.e., engage in an effective creative process.